The influence of civic education learning and the Pancasila Student Profile Program on improving Ideological values understanding - Pangalila, Theodorus; Fatimah, Siti (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Civic Education Learning and the Pancasila Student Profile are important elements in efforts to strengthen students' understanding of Pancasila values. This study aims to: 1) test and analyze whether Civic Education Learning (X1) partially has a significant effect on increasing students' understanding of Pancasila values (X2); 2) test and analyze whether the Pancasila Student Profile Programme (X2) partially has a significant effect on increasing students' understanding of Pancasila values (Y); and 3) test and analyzing whether Civic Education Learning (X1) and the Pancasila Student Profile programme (X2) simultaneously have a significant influence on increasing students' understanding of Pancasila values (Y). This research uses quantitative methods. The research location was Gonzaga Tomohon Catholic Middle School, with a total sample of 40 students. Primary data was obtained through a questionnaire and then tested with the IBM SPSS programme version 26. This study uses multiple linear analysis techniques in hypothesis testing. The results showed that 1) testing the first hypothesis was accepted, namely Civic Education Learning (X1) had a significant effect on increasing students' understanding of Pancasila values (Y); 2) testing the second hypothesis was accepted, namely the Pancasila Student Profile Programmeme (X2) had a significant effect on increasing students' understanding of Pancasila values (Y); and 3) testing the third hypothesis was accepted, namely Civic Education Learning (X1) and the Pancasila Student Profile Programmeme (X2) simultaneously had a significant influence on increasing students' understanding of Pancasila values (Y). Research efforts to contribute to increasing students' understanding of the importance of Pancasila values need to be carried out as an effort to form and strengthen the character of nationalism in the younger generation.